Lectotypification of Alysicarpus gracilis (Papilionoideae: Leguminosae) - Tiwari, Arjun Prasad; Shukla, Achuta Nand; Khanna, Krishna Kumar; Sikarwar, Ram Lakhan Singh (Phytotaxa, 2020)
The genus Alysicarpus Necker ex Desvaux (1813: 120) includes ca. 35 species and 20 infra specific taxa distributed in almost all tropical and subtropical regions of the Old World (Pedly 2001, Lewis et al. 2005, Hassemer et al. 2017, Leeratiwong et al. 2017, Pokle 2017, Dalavi et al. 2019). It is represented in India by about 18 species and nine infra specific taxa, of which seven species and eight infra specific taxa are endemic (Sanjappa 1992, Pokle 2002, Dhabe 2013, Singh et al. 2015, Gholami et al. 2017, Pokle 2017, Dalavi et al. 2019). Alysicarpus species are annual or perennial herbs; leaves generally 1-foliolate or ‘very rarely’ pinnately 3-foliolate; scarious stipules; ebracteolate flowers; scarious calyx with complex venation and turgid articles of its indehiscent pods (Gholami et al. 2016).